(untitled) (International Journal of Environmental Sciences, 2025)
Clustering strategies are frequently used in Wireless Sensor Networks (WSNs) to reduce energy consumption and accommodate the effective functioning of the network. The Hybrid Energy-Efficient Distributed (HEED) protocol is one of them, where residual energy and communication cost are considered as major factors to select cluster heads (CHs). However, HEED fails to consider node mobility as a significant constraint that is apparent in dynamic environments, causing unstable clusters and increases in energy consumption caused by frequent CH changeovers. In order to tackle this challenge, an enhanced version of Mobility-aware HEED (M-HEED) is introduced. This version will add an element of mobility to the process of choosing a CH, which is based on the speed of the nodes. Slower-moving nodes will be favoured as CHs. The goal is to reduce the number of times clusters are reformed and make them as consistent as possible. We compare the key performance indicators of HEED and M-HEED using the Packet Delivery Ratio (PDR), the CH lifespan, and the amount of energy used. The simulators show that M-HEED is a better option for mobile WSN settings because it is more stable, uses less energy, and sends data more consistently.